Sosialisasi Penerapan Literasi Ekonomi sebagai Penguatan Karakter Siswa SMA Negeri 2 Kairatu, Maluku - Latuserimala, Gerald; Ansiska, Paisal (Jurnal Pengabdian Arumbai, 2023)
Character education focuses on positive values, ethics, and critical thinking, not just academic knowledge. In the modern era, which is influenced by technology and globalization, strong character, integrity, empathy, and critical thinking are essential. Economic literacy equips students with the ability to make wise economic decisions, shaping them into better individuals with strong character and the ability to contribute positively to their environment. The purpose of this community service activity is to enhance students' understanding of economic literacy concepts, provide them with essential economic knowledge, and encourage the development of strong and responsible character. The methods used in this activity include socialization and discussions. The success of the activity was measured using pre-test and post-test data, analyzed through the Paired Samples Test. The socialization of economic literacy implementation as a means of strengthening student character was successfully conducted. The significance value (Sig.) of 0.00, which is < 0.05, indicates that this community service activity had a significant impact on students' understanding of economic literacy. This activity had a positive effect, helping to improve students' comprehension of economic concepts while simultaneously strengthening their character.